The influence of tendon compliance on muscle power output and efficiency during cyclic contractions - Lichtwark, G. A.; Barclay, C. J. (The Journal of Experimental Biology, 2009)
Muscle power output and efficiency during cyclical contractions are influenced by the timing and duration of stimulation of the muscle and the interaction of the muscle with its mechanical environment. It has been suggested that tendon compliance may reduce the energy required for power production from the muscle by reducing the required shortening of the muscle fibres. Theoretically this may allow the muscle to maintain both high power output and efficiency during cyclical contraction; however, this has yet to be demonstrated experimentally. To investigate how tendon compliance might act to increase muscle power output and/or efficiency, we attached artificial tendons of varying compliance to muscle fibre bundles in vitro and measured power output and mechanical efficiency during stretch—shorten cycles (2 Hz) with a range of stretch amplitudes and stimulation patterns. The results showed that peak power, average power output and efficiency (none of which can have direct contributions from the compliant tendon) all increased with increasing tendon compliance, presumably due to the tendon acting to minimise muscle energy use by allowing the muscle fibres to shorten at optimal speeds. Matching highly compliant tendons with a sufficiently large amplitude length change and appropriate stimulation pattern significantly increased the net muscle efficiency compared with stiff tendons acting at the same frequency. The maximum efficiency for compliant tendons was also similar to the highest value measured under constant velocity and force conditions, which suggests that tendon compliance can maximise muscle efficiency in the conditions tested here. These results provide experimental evidence that during constrained cyclical contractions, muscle power and efficiency can be enhanced with compliant tendons.